Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Toko Tasya Butik Tebing Tinggi Serta Dampaknya Pada Loyalitas Konsumen - Sari, Dea Novita; Nainggolan, Benhart; Barus, Ben Setiawan (Management And Business Progress, 2023)
This study aims to determine and analyze the effect of product quality and service quality both simultaneously and partially on purchasing decisions and their impact on consumer loyalty at the Tasya Butik Tebing Tinggi store. The method of determining the sample used in this study is to use the Cochran formula as many as 96 samples are consumers of Tasya Butik Stores. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Product Quality variable (X1) has an effect on the Purchase Decision variable (Z). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is accepted, meaning that the service quality variable (X2) affects the purchasing decision variable (Z). Based on the results of the analysis of hypothesis 3, it is concluded that the third hypothesis is accepted, meaning that Product Quality (X1) and Service Quality (X2) have a simultaneous (simultaneous) effect on Purchase Decisions (Z).